IEC 61499 as an Enabler of Distributed and Intelligent Automation: A State-of-the-Art Review—A Different View - Kleanthis Thramboulidis (Journal of Engineering)
The industrial and research activities around the IEC 61499 architecture for distributed automation systems are discussed by Vyatkin, (2011). Research results related to the design of this kind of systems as well as to the execution of IEC 61449 on embedded devices are reviewed. It is claimed that IEC 61499 has been developed to enable intelligent automation through the distribution of software components and that the industry will benefit through its adoption from the promise of the intelligence automation research results. In this paper, several observations are presented on the arguments that are used to prove that IEC 61499 is a solid technology for industrial automation systems development. Portability, interoperability, code modularity, reusability, and reconfigurability as well as determinism and the event-driven execution of IEC 61499 are discussed.